Protective Efficacy of H Antigen from Histoplasma capsulatum in a Murine Model of Pulmonary Histoplasmosis - Deepe, George S. (American Society for Microbiology, 2001)
We previously reported that immunization with H antigen from Histoplasma capsulatum did not protect mice against an intravenous challenge with yeasts. Here, we investigated the utility of H antigen to protect mice in a model of pulmonary histoplasmosis. Mice immunized with H antigen and challenged intranasally 4 weeks postvaccination were protected against sublethal and lethal challenges with H. capsulatum yeasts. If the challenge was performed 3 months after vaccination, there was a reduction in fungal burden following sublethal challenge and a modest delay in mortality in mice given a lethal inoculum. Vaccination was associated with production of gamma interferon, granulocyte-macrophage colony-stimulating factor, interleukin-4, and interleukin-10 by splenocytes. Vaccination with H antigen was not accompanied by a major expansion of CD4(+) or CD8(+) cells in spleens of mice. These results demonstrate that H antigen may be useful as a protective immunogen against pulmonary exposure to H. capsulatum.